Credit crunch and insurance consumption : the aftermath of the subprime mortgage crisis - Kamiya, Shinchi (2021)
Using cross-state panel data of the U.S. personal auto insurance premiums from 2007 to 2012, this study provides evidence that consumer purchases of insurance were reduced by more than expected from losses of risk exposure during and after the subprime mortgage crisis. Analyses show that the credit crunch of auto loans and a deterioration of net worth in housing resulting from the bursting housing bubble contributed to the reduced consumption of auto insurance. This result is robust even after controlling for associated factors, such as the insurance price, personal spending on vehicles, and general consumption. These findings provide evidence for a real effect of the financial crisis.